Activities of mining and metallurgical industry enterprises of the Republic of Kazakhstan: environmental problems and possible solutions - Alimbaev, T.; Mazhitova, Zh.; Beksultanova, C.; Tentigul Kyzy, N. (E3S Web of Conferences, 2020)
The paper discusses the issues related to modern environmental problems that have arisen in connection with the activities of the mining and metallurgical industry enterprises of the Republic of Kazakhstan. The authors emphasize that due to the industrial progress of the mining and metallurgical industry, which is one of the main sectors of the republic’s economy, the level of environmental pollution is increasing. The contributing authors prove by examples that, on the one hand, the growth of the economic potential of the mining and metallurgical industry and the transition to market mechanisms for the development of the economy have generated a large increase in the potential of the republic as a major exporter and leader among the world's raw material powers. On the other hand, the increase in industrial production led to a real threat of an environmental crisis in the republic. We conclude that it is possible to solve the environmental problems by improving measures to protect atmospheric air and increasing the efficiency of water resources use and protection. In addition, according to the authors, reduction in the chemical load on the soil, strengthening of the work on protection, reproduction and rational use of the plant and animal world, the introduction of treatment facilities and plants, especially in places of mining, will create a favorable environment for a significant improvement in environmental situation in the region.